Synergistic suppression of apoptosis in salivary acinar cells by IGF1 and EGF - Limesand, KH (2003)
Tissue homeostasis requires balancing cell proliferation and programmed cell death. IGF1 significantly suppressed etoposide-induced apoptosis, measured by caspase 3 activation and quantitation of cellular subG(1) DNA content, in rat parotid salivary acinar cells (C5). Transduction of C5 cells with an adenovirus expressing a constitutively activated mutant of Akt-suppressed etoposide-induced apoptosis, whereas a kinase-inactive mutant of Akt suppressed the protective effect of IGF1. IGF1 also suppressed apoptosis induced by taxol and brefeldin A. EGF was unable to suppress apoptosis induced by etoposide, but was able to synergize with IGF1 to further suppress caspase 3 activation and DNA cleavage after etoposide treatment. The catalytic activity of Akt was significantly higher following stimulation with both growth factors compared to stimulation with IGF1 or EGF alone. These results suggest that a threshold of activated Akt is required for suppression of apoptosis and the cooperative action of growth factors in regulating salivary gland homeostasis.